SPECIFYING THE CONSPICUOUS FEATURES OF THE OZONE LAYER DEPLETION FOR PAKISTAN’S ATMOSPHERIC REGION - Yousuf Zai, M.A. K.; Qaumar, J.; Ansari, M.R. K. (The Nucleus, 2020)
Events such as the huge industrial emissions of Chlorofluoro Carbons (CFCs) provide almost visible example of man-made atmospheric pollution and global unbalance of the natural ecology. Among other scientific and socio-economic fallouts from this, the phenomenon of ozone layer depletion (OLD) is particularly disturbing. It has already attracted wide attention throughout the globe by way of 1987 Montreal protocol. This paper looks into the effectiveness of autoregressive model and predicts the menacing influence of the OLD. As such, with reference to the data for stratospheric region of Pakistan, this communication presents the confidence interval for the population mean of OLD for a significant level of probability. Then it considers the estimation of autoregressive model of order one for forecasting time series on monthly basis from 1970 to 1994, by identifying a set of related predictors. Autoregressive technique produces fairly accurate results as compared to the least squared estimate. We also consider the issue of validating the model by displaying predicted and observed data, by residual analysis, and by autocorrelation functions.